INTEGRATION OF EDUCATION AND INFORMATION RESOURCES OF HIGHER EDUCATION WHEN ORGANISATING SELF-STUDY WORK OF THE FUTURE PHARMACEUTISTS IN ORGANIC CHEMISTRY - Головченко, Оксана Іванівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article substantiates the feasibility of integrating the education and information resources of medical (pharmaceutical) of higher education institutions (Medical (Pharmaceutical) Higher Education Institutions (M(P)HEIs)) when organisating self-study work of the future pharmaceutists in Organic Chemistry. The study relied on the research methods which were as follows: a logic and structural analysis to distinguish the terms and concepts that were used for designation of the information component of the education environment of M(P)HEIs; a terminological method that was aimed at defining the author’s position regarding the interpretation of the concept of “educational information environment of M(P)HEI”; a survey method (online questionnaire-based) that was intended to clarify the main challenges arising when organising self-study work in Organic Chemistry in the settings of extraterritorial interaction of participants in the educational process; an analytical-system method for specifying directions of improvement of the methodology of organising self-study work of pharmaceutists in Organic Chemistry based on the integration of resources of information and educational environment of M(P)HEIs. The study has worked out the author’s interpretation of the concept of “educational information environment of M(P)HEI” as a systematically organised set of conditions for the implementation of an effective and safe educational process, which involves purposeful, the dynamic interaction of its participants based on the use of computer-aided learning tools to form general and professional competencies in future healthcare professionals. Having used the results of the online survey involving 108 full-time students of the Pharmaceutical Faculty of Bogomolets National Medical University, it was found feasible to combine the domains which are as follows: information obtained through electronic resources and services (educational (educational) portal; the MOODLE system with an e-learning course in the discipline; an environment for practical assignments; the environment for project-purpose work organisation (Microsoft Office 365, G Suite); social networks, using the Facebook account for the specialism department as the example, with academic texts (textbooks, tutorials, guidelines, scientific articles, etc.) on the main topics of the course of “Organic Chemistry”